2010
DOI: 10.1111/j.1365-2133.2010.09694.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor and low-density lipoprotein on proliferation and migration of keratinocytes

Abstract: Pitavastatin significantly upregulates LDLR in both NHKs and C57BL6 mouse skin, resulting in increased keratinocyte proliferation. LXRbeta may be involved in the pitavastatin-induced keratinocyte proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Copyright © 2021 IR Research Publication -All Rights Reserved Cholesterol carrier proteins play important roles in delivering the required cholesterol needed for the cell. Previous studies have shown that cholesterol improves the proliferation and migration of keratinocytes (10). In the present work, we have examined the role of LDL and pitavastatin on migration and cholesterol-mediated protein expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Copyright © 2021 IR Research Publication -All Rights Reserved Cholesterol carrier proteins play important roles in delivering the required cholesterol needed for the cell. Previous studies have shown that cholesterol improves the proliferation and migration of keratinocytes (10). In the present work, we have examined the role of LDL and pitavastatin on migration and cholesterol-mediated protein expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 94%
“…Low-density lipoprotein (LDL) is associated with cholesterol deposition in peripheral vessels and plaque formation, resulting in a high risk for atherosclerosis and heart disease (15,16), and elevated LDL is a common reason for statin therapy. We chose pitavastatin in this study as it was shown to upregulate LDLr in cultured keratinocytes as well as mouse epidermis (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective cholesterol homeostasis in keratinocytes and dermal fibroblasts is needed to sustain the integrity of cutaneous permeability barrier function [41][42][43][44] and to provide one of the key membrane components needed for cellular proliferation and migration [45][46][47][48]. Here, cholesterol efflux was used primarily as confirmation of cellular responsiveness to HDL (Figure 2), but some interesting findings emerge, most notably that efflux from neonatal dermal fibroblasts was lower than that observed in adult dermal fibroblasts and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicate that the low-density-lipoprotein (LDL) receptor was expressed on the epidermis [ 22 , 23 ]. The LDL receptor was expressed at a higher level in the psoriasis skin than in the normal skin [ 24 , 25 ]. Human low-density lipoprotein is the major lipid protein complex in the blood for the transport of lipids throughout the body.…”
Section: Discussionmentioning
confidence: 99%